Acquisition of Email Service Based Android Using NIST - Rusydi Umar; Imam Riadi; Bashor Fauzan Muthohirin (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Email is one of the results of the development of information and communication technology. Email is widely used to exchange information by sending and receiving data, such as document files, images, correspondence and others. With the development of technology and information causing crimes in communicating also growing, the perpetrators of cyber crime commonly referred to as cybercrime. Any crime committed by cybercrime will surely leave the evidence, in this study will make the acquisition of android-based email using the method of national institute of standards and technology (NIST). The results obtained IP address of the sender's email header as digital evidence.